Responsible behaviour or business? Social responsibility (CSR) in sport management - Molnár, G.; Ráthonyi-Ódor, Kinga; Borbély, A. (Applied Studies in Agribusiness and Commerce, 2013)
CSR has become increasingly important in today’s business world and managers must consider not only the economic results of their decisions but also the legal, ethical, moral, and social impact and repercussions of each of their decisions. Some multinational companies’ CSR activities even clearly represent applicability of CSR in sport management. The aim of this study was to do a critical comparative analysis, present the changes, alterations in the traditional company philosophy, objectsystem; then to define the concept of CSR, its importance in sport, finally to analyze some of the top 20 World Food & Beverage Companies’ (Coca-Cola, Danone, Nestle) CSR activities in sport management. Similarly to the whole economics – beside traditional theoretical tendencies, parallel to them and not developing them – a new kind of company theory concerning the long-term balance problems of the natural environment and society is being formed. Although the notion of corporate social responsibility (CSR) is prominent in some of the current discussions and investigations about the role of business in society, the concept – integrate social and environmental aspects in their business activity – is not new. According to the websites and sustainability reports of the international parent companies and domestic subsidiaries, we can say, that the companies show similarity at several points with regard to social responsibility within the field of sport management. However we must emphasize that we can find in the domestic practice fewer examples. In this case probably the media plays important role, which prefer the news of scandals such as CSR-related initiatives. In the public the companies’ CSR activities are even less known. Finally we can establish, that about the sport sponsorship the parent companies we have more information, their reports and websites are more transparency. In contracts, in the case of subsidiaries we can meet deficiencies.